Effects of medial meniscal slope and medial posterior tibial slope on the locations of meniscal tears: A retrospective observational study. Issue 47 (20th November 2020) - Wang, Xiaotan; Jing, Lizhong; Wang, Xiaole; Li, Zhen; Li, Zhuang; Zhang, Zhiwei; Yang, Jiushan
Abstract : Abstract: The aim of this study was to analyze the relationship between medial posterior tibial slope (MPTS) and medial meniscus slope (MMS) with the location of meniscal lesions. We hypothesize that meniscuses with greater MPTS and MMS are more likely to have lesions in posterior horn. A total of 292 patients underwent arthroscopic surgery between January 2014 to September 2019 due to knee osteoarthritis (OA) and meniscal lesions were reviewed. Based upon the location of meniscal tears, patients were categorized as group B (tears in posterior horn) and group A (other sites). MPTS and MMS were measured from magnetic resonance imaging (MRI) slices. Osteoarthritis grade was evaluated in anteroposterior radiographs by the criteria defined by Kellgeren and Lawrence. Demographic data, OA grade, MPTS, and MMS for the 2 groups were compared and analyzed. The group A had 29 (39%) male and 45 (61%) female subjects with a mean age of 57.07 ± 6.79 years. Group B consists of 74 (34%) male and 144 (66%) female subjects with a mean age of 58.90 ± 7.594 years. ( P  = .067 and P  = .458 for age and sex, respectively). In group A, 31 knees (42%) were determined to be Kellgren–Lawrence grade one, 32 knees (43%) grade two, and 11 knees (15%) grade three. In group B, 86 knees (39%) were categorized in grade one, 85 knees (39%) in grade two, and 47 knees (26%) in grade three ( P  = .085). The mean MPTS was 5.06 ± 2.11 degree for group A and 6.15 ± 2.37 degree for group B ( P  = .001). The mean MMS for group A was lower than group B (1.38 ± 2.12 degree vs 3.14 ± 2.92 degree; P  < .000) This study demonstrated that increased MPTS and MMS may be considered as the risk factors for medial meniscal posterior horn tears.